Is it worth teaching vocabulary?. Issue 4 (9th November 2020) - Nation, Paul
Abstract: Most teachers are concerned about the teaching of vocabulary. However, it is much more effective to focus on the ways in which vocabulary can be learned. This article looks at the jobs of the teacher, which include, in order of importance, (1) designing a balanced course, (2) organizing classroom work and homework, (3) training the learners in how to learn, (4) testing, and (5) teaching vocabulary. These jobs apply to the learning of vocabulary through independent study and learning through language use. There is a brief description of the author's ideal vocabulary learning program, which includes a balance of learning opportunities.